Expert System for Diagnosing Broccoli Plant Diseases Using the Certainty Factor Method - Nasution, Yusuf Ramadhan; Santoso, Heri; Lbs, Rahma Tania Mawaddah (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
Broccoli farmers or novice broccoli growers have problems knowing the diseases that attack their broccoli plants. Because of this problem there is often a delay in handling which can cause death and can also transmit disease to other broccoli plants so that disease in plants causes a decrease in crop quality and yield. Efforts made to assist farmers in cultivating broccoli plants quickly provide information to farmers so that they know about plant diseases that attack the plants they are treating with a system that can make it easier for farmers to find out earlier about the condition of broccoli plants. The system that was built uses the assurance factor method to get accurate disease diagnosis results. The application is made in the form of an expert system that is useful for diagnosing broccoli plant diseases besides that it will make it easier for farmers to find solutions for handling broccoli plants.